INTEGRASI ATRIBUT PRODUK DAN DAYA TARIK BRAND AMBASSADOR DALAM MEMBENTUK LOYALITAS PELANGGAN PRODUK K-FOOD - Wisnu Mahendri; Khofifah Sari (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2026)
This study examines the effects of brand ambassadors, brand image, and taste on customer loyalty for Mie Sedaap Selection Korean Spicy Chicken in Jombang Regency, with purchasing decisions as a mediating variable. Using a quantitative approach and SEM-PLS analysis, questionnaires were distributed to 150 consumers. The results show brand ambassadors positively and significantly affect both loyalty and purchasing decisions. Brand image has a positive but insignificant impact. Taste significantly affects purchasing decisions but not loyalty directly. Purchasing decisions are key to driving loyalty and mediate the effect of taste, but not brand ambassadors or brand image. The study concludes customer loyalty is more influenced by satisfying purchase and consumption experiences than by brand image. Practically, maintaining taste consistency, encouraging repeat purchases, and using promotional figures are crucial in a competitive market.